Characterization of small leucine-rich proteoglycans in aortic valves of patients with aortic valve stenosis. Issue 5 (2016) - Furukawa, Hiroshi; Chikada, Masahide; Yokoyama, Michiyo K.; Arito, Mitsumi; Kurokawa, Manae S.; Sato, Toshiyuki; Sato, Masaaki; Omoteyama, Kazuki; Suematsu, Naoya; Kobayashi, Toshiya; Sagane, Masahiro; Suzuki, Hirotoshi; et al.
No abstract available